Diseño de programas radiales municipales para la defensa y conservación del medio ambiente del cantón Quilanga - Jimenez Avila, Enidt Maribel (2015)
This research work was made in Canton Quilanga belonging to the province of Loja based on the following problem: DESIGNING LOCAL RADIO PROGRAMS FOR DEFENCE AND ENVIRONMENTAL PROTECTION OF CANTON QUILANGA? the same was selected because of the importance it represents in the canton. The methods used for the development of the research were: scientific, analytical synthetic, inductive, deductive and literature. Surveys to gather information was used a hundred informants quality, which allowed obtaining the information needed for field research. From the responses it was concluded that: All surveyed (100%) consider that it is vital to strengthen the environmental protection in this town, since most do not have a large learning about this, and therefore do not They can apply specific actions to help protect the environment. According to the criteria given in the interview conducted Quilanga Mayor of Canton, it was determined that there are no oriented programs educate people. The recommendations seek the Municipality through agreements promote the design and implementation of radio programs intended for the transmission of issues related to the environment. Finally the dissemination of the radio program is to "take care of our environment," the same as surely contribute to raise awareness and thus the protection of the environment in the aforementioned canton.